Investigation of the effects of extraction temperature and time on bioactive compounds content from garlic (Allium sativum L.) husk - Thach, Nguyen Ai (Frontiers in Sustainable Food Systems, 2022)
Garlic (Allium sativum L.) has been used as a functional food and medicine in traditional prescription for centuries. The extract of garlic husks contains phytonutrients and antioxidant capacity, which can be applied in the food, nutraceutical, cosmetics, and pharmaceutical industries. However, garlic husks, the by-product from food industry, are considered as agricultural wastes. Hence, this research aims at evaluating the content of several compounds in the extract of garlic husks and determining the appropriate temperature and time for the extraction processing of bioactive compounds from garlic husks. In this research, garlic husk powder was extracted different temperature from 40 to 80oC during the time duration from 30 to 120 minutes. This study found that the optimum temperature was from 60 to 70oC and time duration was from 60 to 90 minutes for the extraction process. The optimal content of total polyphenols content of 8.93±0.252 mg gallic acid equivalent/g, total flavonoids content of 0.028±0.002 (mg quercetin equivalent /g), total thiosulfinates content of 9.73±0.071 (µmol/g) and total anthocyanins content of 0.0047±0.0001 (mg/g) of dried garlic husk). Based on the finding, the study suggests that garlic husk should be utilized as a potential source of natural antioxidants in garlic extract, a food supplement, contains antioxidants to support the cardiovascular and immune systems and odorless garlic products.